PENGARUH MEDIA KOMUNIKASI INTERNET TERHADAP POLA PERILAKU ANAK DI BAWAH 17 TAHUN - Syafruddin Ritonga Wira Andhika (PERSPEKTIF, 2013)
The research wants to explore the effect of internet for children under 17 years. There are positive yet negative effect of internet. This research aim is to describe both effects and make teenagers to be more understanding about internet for their mental health and social life. Through descriptive method, researcher make interview with teenagers age 14-17 who access internet in â€œAmal Netâ€ in Amal St, Medan Sungal. The result of research shows that internet effects behavior pattern of teenagers, positively and negatively. Teenagers able to search information, knowledge that they have not received from teachers. But internet also give negative effect for teenagers (pornography, gambling, and addiction to social network). Through better understanding about pattern of teenagers behavior on using internet will create a better communication relation among teenagers, parents, society, and government.